Analisis Kelayakan Investasi Pembelian Pesawat N219 oleh PT Pelita Air Service untuk Penerbangan Perintis Manokwari, Papua Barat - Arzaq Tahara Fitwantyo; Mukhamad Najib (IPB University, 2020)
PT Pelita Air Service (PT PAS) as a subsidiary of PT Pertamina (Persero) which is engaged in the aviation industry has four business pillars underway. One of PT PAS's main businesses is the air charter business which will later be developed into a pioneer aviation business. By seeing a good growth rate of passengers and to increase the connectivity between areas in Indonesia, the pioneering aviation business will have enormous potential for PT PAS to develop its business. This research was carried out analyze non-financial and financial aspects. The results show that the non-financial aspects of the technical aspects are considered not feasible to do business. As for the aspects of the marketing, management, law, and financial aspects are considered feasible. For the financial aspect, the NPV value is Rp 23.879.575.648, IRR is 20 percent, Net B/C is 1.942, and PP is 9,2 years.